2014
DOI: 10.1055/s-0034-1393959
|View full text |Cite
|
Sign up to set email alerts
|

Heart Transplantation in Patients Older than 65 Years: Worthwhile or Wastage of Organs?

Abstract: Background Patients older than 65 years have traditionally not been considered candidates for heart transplantation. However, recent studies have shown similar survival. We evaluated immediate and medium-term results in patients older than 65 years compared with younger patients. Methods From November 2003 to December 2013, 258 patients underwent transplantation. Children and patients with other organ transplantations were excluded from this study. Recipients were divided into two groups: 45 patients (18%) age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
4
1
Order By: Relevance
“…In this study, the most crucial factor affecting readmission was infection, which is similar to the result of a previous study that revealed that the main cause of death in 1 year after heart transplantation was infection (Prieto, Correia, Batista, & Jesus Antunes, ). Concerning rejection, far more individuals (58%) were readmitted in that study and specifically, those with slight rejection that did not require treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the most crucial factor affecting readmission was infection, which is similar to the result of a previous study that revealed that the main cause of death in 1 year after heart transplantation was infection (Prieto, Correia, Batista, & Jesus Antunes, ). Concerning rejection, far more individuals (58%) were readmitted in that study and specifically, those with slight rejection that did not require treatment.…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study, 22 patients (8.8%) developed cardiac CAV (Prieto et al, 2015), compared with three patients (1.2%) in this study. These differences are thought to be related to the patients' age (65 years or older in Prieto et al, 2015) and to the preventative effects of CAV through appropriate early interventions such as the broad use of statins and new immunosuppressants among the participants of this study.…”
Section: Discussioncontrasting
confidence: 47%
“…Altogether, these data can be interpreted by the concept that although recipient age may not be directly involved in the process of coronary lesions progression, older recipients bear more often multiple comorbidities and metabolic abnormalities that are related to increased risk of “standard” cardiovascular disease, and thus poor outcome. In support of this concept, older recipients with a low comorbidity profile show good outcomes after transplantation .…”
Section: Discussionmentioning
confidence: 84%
“…Of the 48 articles investigating risk factors for CAV, six had a prospective design , seven were subanalysis of multicenter registries , and 36 were retrospective mostly single‐center cohort studies (Table ). In most of the studies, several factors emerged from the analysis as associated with CAV, but it has to be noted that only few were consistently reported in all studies, which analyzed widely variable sets of risk factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation